IDNLearn.com is your reliable source for expert answers and community insights. Join our community to receive prompt and reliable responses to your questions from experienced professionals.
Sagot :
Answer:
at answer C, that's supposed to be x= -4 , 1 and that's the answer.
x^2 + 3x - 4 = 0
Quadratic formula:
x = -b +- sqrt{b^2 - 4ac}/(2a)
Let a = 1
Let b = 3
Let c = -4
Just plug into the quadratic formula and do the math.
We are looking for x.
x = -3 +- sqrt{3^2 - 4(1)(-4)}/2(1)
x = -3 +- sqrt{9 + 16}/2
x = -3 +- sqrt{25}/2
x = (-3 +- 5)/2
Separate x into two parts.
Part 1
x = (-3 -5)/2
x = (-8)/2
x = -4
Part 2
x = (-3 + 5)/2
x = 2/2
x = 1
Answer: x = -4, x = 1
Thank you for joining our conversation. Don't hesitate to return anytime to find answers to your questions. Let's continue sharing knowledge and experiences! Your questions deserve reliable answers. Thanks for visiting IDNLearn.com, and see you again soon for more helpful information.